Lebanon’s Economic Crisis and Its Impact on Refugee Policy (2017-2020) - Muhammad Fauzan Alamari (UNIDA Gontor, 2024)
The enduring refugee crisis in Lebanon is not a novel occurrence, as it has been a destination for refugees since the initial wave of Palestinian displacement. Lebanon, grappling with a significant number of refugee population, has encountered demographic challenges arising from this influx. The situation intensified with the onset of the Arab Spring in the Middle East, leading to an unprecedented surge in refugee numbers entering Lebanon, necessitating careful management. Against the backdrop of Lebanon’s significant economic crisis, this research seeks to emphasize the phenomenon from a perspective that underlines the formulation of foreign policy driven by economic considerations. The dynamics discussed in this article aim to deepen the understanding of the complexities surrounding Lebanon’s economic crisis and its strategies for handling the refugee influx, emphasizing the intricate interplay between economic interests and foreign policy decisions in Lebanon’s response to the enduring refugee crisis. Keywords: Arab Spring, Economic Crisis, Lebanon, Middle East,Refugees.